Biodegradable Polycaprolactone-Titania Nanocomposites: Preparation, Characterization and Antimicrobial Properties - Muñoz-Bonilla, Alexandra (Molecular Diversity Preservation International (MDPI), 2013)
Nanocomposites obtained from the incorporation of synthesized TiO(2) nanoparticles (≈10 nm average primary particle size) in different amounts, ranging from 0.5 to 5 wt.%, into a biodegradable polycaprolactone matrix are achieved via a straightforward and commercial melting processing. The resulting nanocomposites have been structurally and thermally characterized by transmission electron microscopy (TEM), wide/small angle X-ray diffraction (WAXS/SAXS, respectively) and differential scanning calorimetry (DSC). TEM evaluation provides evidence of an excellent nanometric dispersion of the oxide component in the polymeric matrix, with aggregates having an average size well below 100 nm. Presence of these TiO(2) nanoparticles induces a nucleant effect during polymer crystallization. Moreover, the antimicrobial activity of nanocomposites has been tested using both UV and visible light against Gram-negative Escherichia coli bacteria and Gram-positive Staphylococcus aureus. The bactericidal behavior has been explained through the analysis of the material optical properties, with a key role played by the creation of new electronic states within the polymer-based nanocomposites.